Rule of law, misrule of men - Scarry, Elaine (Boston review book., 2010)
This book is a passionate call for citizen action to uphold the rule of law when government does not. Arguing that post-9/11 legislation and foreign policy severed the executive branch from the will of the people, Elaine Scarry in Rule of Law, Misrule of Men offers a fierce defense of the people's role as guarantor of our democracy. She begins with the groundswell of local resistance to the 2001 Patriot Act, when hundreds of towns, cities and counties passed resolutions refusing compliance with the information-gathering the act demanded, showing that citizens can take action against laws that undermine the rights of citizens and noncitizens alike. Scarry, once described in the New York Times Sunday Magazine as "known for her unflinching investigations of war, torture, and pain," then turns to the conduct of the Iraqi occupation, arguing that the Bush administration led the country onto treacherous moral terrain, violating the Geneva Conventions and the armed forces' own most fundamental standards. She warns of the damage done to democracy when military personnel must choose between their own codes of warfare and the illegal orders of their civilian superiors. If our military leaders uphold the rule of law when civilian leaders do not, might we come to prefer them? Finally, reviewing what we know now about the Bush administration's crimes, Scarry insists that prosecution -- whether local, national or international -- is essential to restoring the rule of law, and she shows how a brave town in Vermont has taken up the challenge. Throughout the book, Scarry finds hope in moments where citizens withheld their consent to grievous crimes, finding creative ways to stand by their patriotism.